Effects of preoperative veno-venous extracorporeal membrane oxygenation management and left atrial pressure reduction via balloon atrial septostomy on respiratory system compliance in a neonate with transposition of the great arteries with intact ventricular septum - Keisuke Nishida; Yusuke Seino; Muneyuki Takeuchi (Respiratory Medicine Case Reports)
Background: Transposition of the great arteries with intact ventricular septum causes severe hypoxia immediately after birth. Balloon atrial septostomy is often required for oxygenation improvement, and severe cases may require veno-venous extracorporeal membrane oxygenation (VV-ECMO). This case report highlights the critical role of balloon atrial septostomy in improving respiratory system compliance and facilitating early ECMO discontinuation in a neonate with transposition of the great arteries. Case summary: A neonate with transposition of the great arteries experienced persistent hypoxia, hypotension, and lactic acidosis, prompting VV-ECMO on the first day of life. Echocardiography revealed a restrictive atrial septal defect, and balloon atrial septostomy was performed. This resulted in increased oxygen saturation, improved respiratory system compliance (from 0.19 to 0.43 mL/cmH2O/kg), and reduced left atrial pressure. ECMO was successfully withdrawn on day 2, which was later followed by a successful Jatene procedure. Conclusion: Balloon atrial septostomy can significantly improve oxygenation and respiratory system compliance in patients with transposition of the great arteries, enabling rapid VV-ECMO discontinuation and informing future congenital heart disease management.